2003
DOI: 10.1007/s00203-003-0634-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the different tfd genes for degradation of chloroaromatic compounds in Ralstonia eutropha JMP134

Abstract: Ralstonia eutropha JMP134 possesses two sets of similar genes for degradation of chloroaromatic compounds, tfdCDEFB (in short: tfdI cluster) and tfdDII CII EII FII BII (tfdII cluster). The significance of two sets of tfd genes for the organism has long been elusive. Here, each of the tfd genes in the two clusters on the original plasmid pJP4 was replaced by double recombination with a gene fragment in which a kanamycin resistance gene was inserted into the respective tfd gene's reading frame. The insertion mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Except for chloromuconate cycloisomerases, no great differences in substrate specificity between the enzymes encoded by each tfd module have been found, although it has been shown that the maintenance of both modules in pJP4 results in a higher expression of key catabolic activities that prevents the accumulation of toxic chlorocatechols (28,30). An inactivation analysis of tfd functions was recently reported (19), suggesting that the tfdD II C II E II F II B II genes are not essential for growth on 2,4-D but are relevant for growth on MCPA. Since no further information was given on intermediate accumulation during the degradation of chlorophenoxyacetates by these mutants, and since gene complementation was not reported, it is unclear if some of these phenotypes could be derived from polar effects on the chlorophenol hydroxylase genes.…”
mentioning
confidence: 99%
“…Except for chloromuconate cycloisomerases, no great differences in substrate specificity between the enzymes encoded by each tfd module have been found, although it has been shown that the maintenance of both modules in pJP4 results in a higher expression of key catabolic activities that prevents the accumulation of toxic chlorocatechols (28,30). An inactivation analysis of tfd functions was recently reported (19), suggesting that the tfdD II C II E II F II B II genes are not essential for growth on 2,4-D but are relevant for growth on MCPA. Since no further information was given on intermediate accumulation during the degradation of chlorophenoxyacetates by these mutants, and since gene complementation was not reported, it is unclear if some of these phenotypes could be derived from polar effects on the chlorophenol hydroxylase genes.…”
mentioning
confidence: 99%
“…The best-studied 2,4-D degradation genes (located in a chromosome or a plasmid) are tfd-like (pJP4-like). The very recently sequenced 87,688-bp plasmid pJP4 (48) from Wautersia eutropha JMP134 (formerly Ralstonia eutropha) was originally isolated in Australia (8), and its tfd genes and the corresponding enzymes responsible for converting 2,4-D to 3-oxoadipate are well characterized (22,23,25,26,35,58). Besides pJP4, there are only two cases in which the DNA regions containing tfd genes for the whole 2,4-D degradation pathway have been sequenced, a chromosomal transposon-like structure (about 30 kb) from Delftia acidovorans P4a (15) and Tn5530 (41 kb) located in plasmid pIJB1 from Burkholderia cepacia 2a (36,56).…”
mentioning
confidence: 99%
“…The analysis of the three benzoate pathways in LB400 is a case study of functional redundancy, a recurring theme in studies of LB400 (30) and other large-genome environmental isolates (22,24,34). Where previous studies (12,13) suggested the involvement of the ben-cat, box C , and box M pathways in benzoate catabolism in LB400, the currently reported data provide definitive evidence that each pathway assimilates benzoate.…”
Section: Discussionmentioning
confidence: 78%
“…strain RHA1 (ϳ9.7 Mbp) have shown the presence of multiple pathways that catabolize phthalate, terephthalate, and ethylbenzene (22,34). In Ralstonia eutropha JMP134 (ϳ7.3 Mbp), redundant tfd operons involved in 2,4-dichlorophenoxyacetic acid degradation provide more-efficient degradation of 2-methyl-4-chlorophenoxyacetic acid (24), suggesting that the pathway redundancy confers a selective metabolic advantage.…”
mentioning
confidence: 99%